(untitled) (GEON Journal (Management, Organizations and Business), 2017)
The right direction in the mayorship of Montería in the last eight years, accompanied by large contributions from the general budget of the Nation as a reward for good practices in governance, has brought a high degree of urban growth leveraging turn to the city has become one of the ten largest in the country. Its commercial activity is surprising, as well as meet the demands of its own people, it seeks to create a common ground with the surrounding rural areas. It is remarkable developments in sectors such as hospitality, ecotourism, trade, university education, food and transport; but taking the results of projects submitted and approved at the bottom undertake, Cordoba is ranked 21 of 32 departments studied and has only 7,559 pymes in 19 companies. Who then designs entrepreneurial projects and makes use of the resources of the region? In response, the present research project that seeks to identify the reasons for this worrying lag and progress indicate that citizen born in the city of Monteria is living in a state of comfort and relaxed in front of the few existing companies was raised.